Effectiveness of Mental Health Literacy Interventions for Adolescents: A Systematic Review and Meta-analysis - Guanqi Sun; Chengyi Wang; Junhua Zhang (SAGE Open)
To address the urgent need for effective adolescent mental health support, this systematic review and meta-analysis evaluated the impact of mental health literacy interventions on adolescents, a group highly susceptible to mental health issues. In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registered under the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY202330098), our research thoroughly searched prominent databases, including PubMed, Web of Science, EBSCO, CNKI, Wanfang, and Chongqing VIP. We focused on studies employing a pre-test-post-test design to compare mental health literacy interventions against control groups. Our analysis included 18 studies revealing statistically significant improvements in adolescents’ mental health literacy, knowledge, and help-seeking and a reduction in stigma associated with mental health issues. The effectiveness of these interventions varied significantly across regions, with notable improvements in Asia, particularly in terms of help-seeking and stigma reduction. Interventions featuring frequent interactions proved particularly effective, showing significant increases in mental health knowledge and help-seeking. Multifaceted interventions that combined various methods were most beneficial for enhancing mental health knowledge. Importantly, although the positive effects on mental health literacy and stigma reduction were sustained at the 2-month follow-up, the improvements in help-seeking did not maintain significant levels post-intervention. These findings emphasize the critical need for tailored mental health literacy programs for adolescents and provide novel insights into the efficacy of interactive and diverse intervention strategies.